2020
DOI: 10.1029/2019jc015710
|View full text |Cite
|
Sign up to set email alerts
|

Ice Shelf Basal Melt and Influence on Dense Water Outflow in the Southern Weddell Sea

Abstract: We use new observations of stable water isotopes from a research cruise in early 2017 to highlight ocean‐ice interactions occurring under Filchner‐Ronne Ice Shelf, the largest Antarctic ice shelf. In particular, we investigate the properties of Ice Shelf Water with temperature lower than the surface freezing point, in the Filchner Depression. We identify two main flavors of Ice Shelf Water emerging from beneath the Filchner Ice Shelf, which originate from High Salinity Shelf Water end members with distinct cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 70 publications
3
29
0
Order By: Relevance
“…Based on measurements from the same drill holes as discussed above (Figure 1), Huhn et al (2018) report neon-based GBMW baseline fractions of 1.0%-3.6% directly at the FIS base, and lower fractions of <0.4% near the bottom of the northern FIS and in Filchner Trough in 2016. These values are consistent with the (stable oxygen isotopes-based) fractions of 0.4% in Filchner Trough in 2017 reported by Akhoudas et al (2020). In 2018, the FIS front was dominated by ISW, coincident with the highest water mass age (Figure 9) and elevated GBMW fractions of 0.8%-1.0% below a depth of 600 m. These fractions directly agree with the fractions measured by Huhn et al (2018, see their Figure 3) at the northern FIS drill hole sites.…”
Section: On the Hydrographic Transition Between 2017 And 2018 At The Fis Frontsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on measurements from the same drill holes as discussed above (Figure 1), Huhn et al (2018) report neon-based GBMW baseline fractions of 1.0%-3.6% directly at the FIS base, and lower fractions of <0.4% near the bottom of the northern FIS and in Filchner Trough in 2016. These values are consistent with the (stable oxygen isotopes-based) fractions of 0.4% in Filchner Trough in 2017 reported by Akhoudas et al (2020). In 2018, the FIS front was dominated by ISW, coincident with the highest water mass age (Figure 9) and elevated GBMW fractions of 0.8%-1.0% below a depth of 600 m. These fractions directly agree with the fractions measured by Huhn et al (2018, see their Figure 3) at the northern FIS drill hole sites.…”
Section: On the Hydrographic Transition Between 2017 And 2018 At The Fis Frontsupporting
confidence: 92%
“…The 2018-conditions contrast with those observed one year earlier in 2017, when a CTD and stable isotope tracer survey found that Berkner HSSW-sourced ISW dominated in Filchner Trough (Akhoudas et al, 2020). These two different hydrographic conditions are referred to as Berkner-and Ronne-modes, and are mainly manifested by contrasting hydrographic conditions underneath the northern FIS and in Filchner Trough, as schematically illustrated in Figure 11.…”
Section: On the Hydrographic Transition Between 2017 And 2018 At The Fis Frontmentioning
confidence: 82%
“…During this period, observed source water salinities (Methods) between 34.84 g kg −1 (34.65 psu) and 34.87 g kg −1 (34.7 psu) at FNE1 and FNE2 (Fig. 2c ) compare well with the Berkner HSSW 21 , 26 that is found on the shallow continental shelf between the Filchner and Ronne ice shelves north of Berkner Island 27 .
Fig.
…”
Section: Resultsmentioning
confidence: 61%
“…Neglecting minor corrections due to heat conduction at the ice–ocean interface, the slope of these lines is given as , with specific heat capacity of seawater J kg −1 K −1 and latent heat of fusion J kg −1 and salinity of the seawater that is being in contact with the ice. In particular, in absence of other freshwater sources or T–S end-members, Gade-line theory can be used to invert for the open ocean water mass type that has been the source water for a given ISW type, as e.g., done by 26 to discriminate between Berkner HSSW and Ronne HSSW source water types for FRIS ISW. Assuming that ISW being observed at the mooring sites originated from HSSW on the continental shelf, the “source water salinity” of this HSSW is found as the intersection of the ISW’s Gade-line with the surface freezing point temperature.…”
Section: Methodsmentioning
confidence: 99%
“…3A). On the continental shelf in the Filchner Depression (75-78 S), the 28.37 kg m 3 g n surface is associated with very depleted d 18 O values, as a result of the influence of glacial meltwater in this region36 . As this water-mass flows out along the continental slope following the clockwise circulation of the gyre, it quickly loses its d 18 O signature(Fig.…”
mentioning
confidence: 99%